DBN-based ionic liquids with high capability for the dissolution of wool keratin. Issue 4 (12th January 2017) - Liu, Xue; Nie, Yi; Meng, Xianglei; Zhang, Zhenlei; Zhang, Xiangping; Zhang, Suojiang
Abstract : Effects of ILs structures on the dissolution capability were systematically studied, and the optimal IL [DBNE]DEP with high dissolution capability for goat wool was finally obtained. Abstract : An increasing interest has been manifested in the use of ionic liquids (ILs) as solvents for the dissolution of wool keratin due to their tunable and excellent properties, despite the fact that it is still a challenge that ILs with different structures have distinct dissolution capabilities for wool. In this study, a series of 1, 5-diazabicyclo[4.3.0]-non-5-ene (DBN)-based ionic liquids with different anions have been designed and employed for the dissolution of wool keratin. The effects of the ILs structures on their dissolution capabilities were systematically studied, and the optimal IL with high dissolution capability for goat wool was finally obtained by overall considering the time taken for the goat wool complete dissolution and the properties of the regenerated keratin. It was found that both cations and anions, acting as the regulators for polarity ( E NT) and hydrogen-bond basicity ( β ) of the ILs, have significant influence on the dissolution capabilities of the ILs, which play an important role in the design and synthesis of new functional ILs for the dissolution of wool keratin. Furthermore, the time taken for the complete dissolution of 8 wt% goat wool in the optimum IL 1-ethyl-1, 5-diazabicyclo[4.3.0]-non-5-enium diethylphosphate ([DBNE]DEP) is 3 h at 393 K, and the relative crystallinity, content of α-helix, and decomposition temperature of the regenerated keratin from [DBNE]DEP are higher (60.99%, 57.88%, and 521 K, respectively) than that from other ILs. Moreover, the break ratio of the disulfide bond is reduced to only 53.46%. In addition, [DBNE]DEP could be easily reused at least 5 times with stable structures and good dissolving ability, and the non-newtonian index, n, of the DEP IL/keratin solutions is all about 0.8, which means that the DEP IL/keratin solution has good prospects in terms of spinning.